2013
DOI: 10.1007/s12127-013-0128-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the multiple benefits offered by ion mobility-mass spectrometry in oil and petroleum analysis

Abstract: International audienceIon mobility-mass spectrometry is starting to be considered as a useful tool in the deconvolution of complex oil and petroleum samples. While ultrahigh resolution mass spectrometry is the incumbent technology in this field, ion mobility offers complementary information related to species size and shape, and also the ability to resolve structural isomers. In this work, a sample of the resins portion of the Saturates, Aromatics, Resins, and Asphaltenes (SARA) fractions of crude oil was anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 52 publications
1
40
0
Order By: Relevance
“…7, 35 Advancements in IM-MS-based technologies have improved sample separation efficiency by incorporating shape and size-based dimensionality, and are amenable for high (TOF-MS) and ultra-high (FT-MS) mass analyses of petroleum substances. 16, 36 Collectively, these approaches are defined under the term petroleomics; they are useful for detailed chemical characterization to meet regulatory requirements towards grouping of petroleum substances for read across. 7, 10, 15, 37 …”
Section: Discussionmentioning
confidence: 99%
“…7, 35 Advancements in IM-MS-based technologies have improved sample separation efficiency by incorporating shape and size-based dimensionality, and are amenable for high (TOF-MS) and ultra-high (FT-MS) mass analyses of petroleum substances. 16, 36 Collectively, these approaches are defined under the term petroleomics; they are useful for detailed chemical characterization to meet regulatory requirements towards grouping of petroleum substances for read across. 7, 10, 15, 37 …”
Section: Discussionmentioning
confidence: 99%
“…In the past years, various approaches have try to overcome this issue by coupling chromatographic techniques, such as gas and liquid chromatography, 18 or more recently ion mobility spectroscopy. [19][20][21][22][23][24] The number of publications using gas chromatography (GC) coupled to ambient pressure ionisation ultrahigh resolution mass spectrometry is still limited. Recently, Benigni et al have shown the utilisation of atmospheric pressure laser ionisation (APLI) coupled to ICR-MS for increasing the polycyclic aromatic hydrocarbon coverage in petroleum sample material.…”
Section: Introductionmentioning
confidence: 99%
“…14 Previous studies in crude oil research tried to circumvent the problem by combining data from analyses using IMS-TOF MS and FT-ICR MS both after electrospray ionization. [15][16][17][18] Due to the Figure 1. Schematic view of the experimental setup regarding the source region; left and center panel show a section through the source block from a top view with mounted FAIMS unit.…”
Section: Introductionmentioning
confidence: 99%